“Green Destination Tourism” Reviewed from Islamic Economic Perspective (Case Study in Pulesari Yogyakarta Tourist Village) - Robist Hidayat; Taufik Riza Mahendra; Intan Octavia (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Natural tourism villages usually carry the concept of